2014
DOI: 10.1080/19476337.2014.971346
|View full text |Cite
|
Sign up to set email alerts
|

Heat stability and thermal properties of calcium fortified milk

Abstract: The objective of the present study was to investigate the effect of calcium fortification on heat stability and thermal properties of toned milk (cow:buffalo 1:1). Four calcium salts -calcium chloride, calcium acetate, calcium hydroxide, and calcium citrate -were used for the fortification of milk. Upon the addition of calcium salts, there was a marked change in milk pH and acidity except when calcium citrate was added. Sensory scores were highest for calcium citrate fortified milk. The heat stability of calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Similar to protein content, no significant difference was obtained between these values of SDS and falling number value. Present SDS values were in agreement with the values obtained by Supekar, Patil and Munjal (2005) and Kaushik et al (2014). The SDS sedimentation value of wheat flours is based on the fact that the gluten protein absorbs water and swells considerably when treated with lactic acid.…”
Section: Optimization Of Flour Amountssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to protein content, no significant difference was obtained between these values of SDS and falling number value. Present SDS values were in agreement with the values obtained by Supekar, Patil and Munjal (2005) and Kaushik et al (2014). The SDS sedimentation value of wheat flours is based on the fact that the gluten protein absorbs water and swells considerably when treated with lactic acid.…”
Section: Optimization Of Flour Amountssupporting
confidence: 91%
“…The data was analysed using the method described by Kaushik, Sachdeva and Arora (2014). Means, standard error of the mean (SEM), linear regression analysis and 95% confidence intervals were calculated using Microsoft Excel 2007 (Microsoft Corp., Redmond, WA).…”
Section: Discussionmentioning
confidence: 99%
“…The milk composition, including milk protein, lactose, and salt, plays a key role on the thermal stability of milk (Crowley, Kelly, & O'Mahony, 2015;Thoh, Pakdeechanuan, & Chanjula, 2017;Wang, Shi, Li, & Lou, 2015). Milk became unstable to UHT processing at lower calcium additions compared to in-container sterilization (Kaushik, Sachdeva, & Arora, 2015; Omoarukhe, ON-NOM, Grandison, & Lewis, 2010). Therefore, it is necessary to determine the milk composition during the lactation period for the development of high added value goat milk products.…”
mentioning
confidence: 99%
“…In order to make a good source of calcium the finished product must ideally contain 10-19% daily value (DV) or 100-190 mg calcium per serving. Standard ice-cream contains 80 mg of calcium per serving or per 60 g (Kaushik et al 2015).Though BME had imparted bitter taste, CG had imparted sweet taste which improved the overall acceptability of product. Similar results reported by Yonis et al (2013) that CG fortified banana stirred yogurt shown highest mean values for over all acceptability at 1% level.…”
Section: Verification Of the Optimum Formulationsmentioning
confidence: 99%
“…Inorganic calcium salts like calcium chloride, calcium carbonate and calcium phosphate displays moderate solubility but their use is restricted due to its bitter and salty taste (Reddy et al 1999). Calcium from dairy products is easily absorbed by intestine due to favourable effect of casein on calcium absorption by inhibiting calcium precipitation by phosphate in intestinal lumen through the action of phosphopeptides coming from enzymatic hydrolysis of casein (Kaushik et al 2015). Due to the above fact calcium from dairy products has higher bioavailability than calcium in vegetables or cereals and further can be fortified with calcium salts in order to meet required daily intake or to reduce calcium deficiency diseases such as osteoporosis, osteomalacia, hypertension, colon cancer and obesity (Gerstner 2003).…”
Section: Introductionmentioning
confidence: 99%